Preparation of North American Type II PRRSV Infectious Clone Expressing Green Fluorescent Protein - Wang, Liyue (Hindawi Publishing Corporation, 2014)
Porcine reproductive and respiratory syndrome virus (PRRSV) is still one of the most important infectious diseases threatening the swine industry. To construct North American type II PRRSV infectious clone containing green fluorescent protein (GFP) gene, we amplify gfp gene, flanked by PRRSV Nsp2 gene fragments upstream and downstream, using overlap PCR method from pcDNA-EF1-GFP plasmid and FL12 plasmid containing PRRSV infectious genome as the templates. The Nsp2 fragment-flanked gfp gene was inserted into Nsp2 gene of the FL12 plasmid by Spe I and Xho I sites to generate PRRSV infectious recombinant plasmid (FL12-GFP) containing gfp gene. The recombinant PRRSV expressing GFP (PRRSV-GFP) was rescued in baby hamster kidney-21 (BHK-21) cells by transfecting PRRSV mRNA synthesized in vitro and amplified in Marc-145 cells. The PRRSV-GFP infectivity and replication capacity were identified. Results showed that, by adopting overlap PCR strategy, the gfp gene was successfully inserted into and fused with PRRSV Nsp2 gene in the PRRSV infectious clone plasmid FL-12 to generate FL12-GFP plasmid. The recombinant PRRSV-GFP was generated through transfecting PRRSV mRNA in BHK-2 cells. Like its parental virus, the recombinant PRRSV-GFP maintains its infectivity to Marc-145 cells and porcine alveolar macrophages (PAMs). This study provides essential conditions for further investigation on PRRSV.